ИНТЕРМЕДИАЛЬНОЕ ИССЛЕДОВАНИЕ ПРОСТРАНСТВЕННЫХ КОНЦЕПТОВ (НА МАТЕРИАЛЕ НЕМЕЦКИХ И РУССКИХ ИСКУССТВОВЕДЧЕСКИХ ТЕКСТОВ) - Glushkova, Irina (İdil : sanat ve dil dergisi, 2013)
This article is devoted to the research of the verbal representation of local art-concepts (modernism in the 20-th century in Germany and Russia). With the purpose to build a structure of local concepts is described a semantic classification of characteristics of graphic frames, are analyzed their metaphoric actualization, emotional perception and affective evaluation as well.